2022
DOI: 10.1177/11297298221095994
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of autologous scaffold-free tissue-engineered vascular graft for hemodialysis access

Abstract: Background: The growing size of the end stage renal disease (ESRD) population highlights the need for effective dialysis access. Exhausted native vascular access options have led to increased use of catheters and prosthetic shunts, which are both associated with high risks of access failure and infection. Emerging alternatives include tissue-engineered vascular grafts (TEVG). Here we present the endpoint results for 10 ESRD patients with the scaffold-free tissue-engineered vascular access produced from sheets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…However, these synthetic materials are recognized as foreign bodies and generate inflammatory reactions [6][7][8]. In this study, we developed an innovative suture made of a non-denatured biological material that has already shown superior biological properties in humans (tissue integration, remodeling, resist infection, and does not elicit an immune response) [26][27][28]. After characterizing the mechanical properties of hydrated CAM-based ribbons, we have shown that twisted/dried ribbons obtained from CAM sheet can be attached to an eyeless surgical needle to produce biological sutures using a standard manufacturing approach (video 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these synthetic materials are recognized as foreign bodies and generate inflammatory reactions [6][7][8]. In this study, we developed an innovative suture made of a non-denatured biological material that has already shown superior biological properties in humans (tissue integration, remodeling, resist infection, and does not elicit an immune response) [26][27][28]. After characterizing the mechanical properties of hydrated CAM-based ribbons, we have shown that twisted/dried ribbons obtained from CAM sheet can be attached to an eyeless surgical needle to produce biological sutures using a standard manufacturing approach (video 1).…”
Section: Discussionmentioning
confidence: 99%
“…This material, called Cell-Assembled extracellular Matrix (CAM), is produced in large culture flasks as a sheet, which can be cut into ribbons that can be assembled in biological textiles [21,22,25]. This biomaterial was successfully implanted in humans as tubes for vascular applications [26][27][28]. Implantation results validated the hypothesis that this completely biological material can integrate with native tissue, be remodeled by the host's cells, and resist infection.…”
Section: Introductionmentioning
confidence: 87%
“…While there will always be a protein turnover in a biological matrix, the strategy is to have a very slow degradation to allow the body to colonize and remodel the graft before it loses mechanical integrity. This was achieved to some degree using autologous and allogeneic, rolled, CAMbased TEVG [16,17,40].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, cell-sheet-based approaches have been used to produce natural blood-vessel-like constructs, some of which have been tested in clinical trials with excellent results [ 108 ]. For example, long-term results from a recent human study with a cell-sheet-derived graft for hemodialysis access showed great promise as an alternative to synthetic grafts [ 109 , 110 ]. However, these approaches require tedious and complex culture and maturation processing.…”
Section: Application Of Elastic Laminae and Elastin-based Materials T...mentioning
confidence: 99%